2019
DOI: 10.3920/wmj2018.2398
|View full text |Cite
|
Sign up to set email alerts
|

Developments in mycotoxin analysis: an update for 2017-2018

Abstract: This review summarises developments that have been published in the period from mid-2017 to mid-2018 on the analysis of various matrices for mycotoxins. Analytical methods to determine aflatoxins, Alternaria toxins, ergot alkaloids, fumonisins, ochratoxins, patulin, trichothecenes, and zearalenone are covered in individual sections. Advances in sampling strategies are discussed in a dedicated section, as are methods used to analyse botanicals and spices, and newly developed comprehensive liquid chromatographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 217 publications
(118 reference statements)
0
29
0
Order By: Relevance
“…In this review, we summarised some common mycotoxin contaminants found in medicinal materials and discussed methods for their detection. Mycotoxin contamination is usually heterogeneous, so screening methods for detecting these contaminants in medicinal products need to have broad coverage across, and samples should be processed carefully (Zhang et al 2018a ; Tittlemier et al 2019 ). However, many existing studies of mycotoxin contamination lack detailed descriptions of how samples are selected and processed.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we summarised some common mycotoxin contaminants found in medicinal materials and discussed methods for their detection. Mycotoxin contamination is usually heterogeneous, so screening methods for detecting these contaminants in medicinal products need to have broad coverage across, and samples should be processed carefully (Zhang et al 2018a ; Tittlemier et al 2019 ). However, many existing studies of mycotoxin contamination lack detailed descriptions of how samples are selected and processed.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, downsizing the sample preparation represents a promising way to be in accordance with green chemistry principles, as it is related to reduced consumption of chemicals/samples, and a reduced generation of toxic waste. Additionally, applying automation concepts helps to overcome the problems frequently related to the offline conventional sample preparation approaches, such as laborious and time-consuming procedures, the manual handling of samples, and in some cases, poor accuracy or precision [17]. Recent trends for mycotoxin analysis seem to prioritize the miniaturization and automation of the sample preparation approach, allowing them to obtain high-throughput analytical methods [20].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, this is one of the most critical techniques that provides much information, allowing for the simultaneous detection of multi-present mycotoxins and emerging mycotoxins or masked metabolites [ 5 ]. However, before the instrumental analysis of mycotoxins can be carried out successfully, a previous sample preparation step is usually mandatory [ 17 ]. For this reason, mycotoxins are extracted from the food matrix and added to a more appropriate media or solvent [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations